Peso y contenido de aceite de las semillas de higuerilla (Ricinus communis L.): Efecto de la posición en el racimo - Ramos, L.C. da Silva; Savy Filho, A; Tango, J.S. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The seed weight and oil content of the castorbean cultivar Guarani and the introduction IPP, were evaluated at the top, middle and lower parts of the raceme. The evaluations were done in order to verify differences along the raceme Significant variations were observed for such characteristics among plants, especially on the apex of the raceme. In general, the seed weight and oil content decreased from the lower to the erpper part of the raceme. Significant differences were found in the IPP introduction in relation to "Guarani " IPP introduction has a long raceme with a greater number of fruits than the Guarani cultivar, and could increase the competition for plant metabolites among fruits on the top, middle and lower part of the raceme. The oil contents must be considered as average values since they were obtained by solvent extraction of several seeds. Individual seed evaluations should present greater differences than the solvent extraction method. Therefore, a standard sampling procedure should be used to obtain representative measurements. The middle and lower part of the raceme appears to be the most suitable for seed sampling. Despite the tendency of seed weight and oil content to decrease from the bottom to the top part of the raceme, no significant correlation was found between such measurements.